Femtosecond laser-assisted astigmatic keratotomy in naturally occurring high astigmatism. Issue 12 (25th November 2009) - Abbey, A; Ide, T; Kymionis, G D; Yoo, S H
Abstract : The technique and a case report of femtosecond laser-assisted astigmatic keratotomy (FS AK) are reported in a patient with naturally occurring high astigmatism. The operation was performed using flap mode software to create two anterior arcuate side cuts in each eye using a femtosecond laser (IntraLase/AMO, Irvine, California; 30 kHz) in a 30-year-old female with a naturally occurring high astigmatism (with-the-rule) of 5.25 D in both eyes. In the right eye, the manifest refraction improved from −3.5+5.25×89 preoperatively, with an uncorrected visual acuity (UCVA) of counting fingers (CF) and a best spectacle-corrected visual acuity (BSCVA) of 20/25, to −1.75+2.75×90 postoperatively, with a UCVA of 20/50 and a BSCVA of 20/20. In the left eye, the manifest refraction improved from −3.5+5.25×83 preoperatively, with a UCVA of 20/200 and a BSCVA of 20/20, to −1.75+2.25×85 postoperatively, with a UCVA of 20/30 and a BSCVA of 20/20.